Authorial Image in Genre of Corporate Websites of Law Firms: A Study of Legal Organizations in Kemerovo Region (Kuzbass) - T. G. Rabenko (Научный диалог)
This study investigates the authorial image presented on the corporate websites of law firms. The authorial image is understood as the representation of the law firm itself, functioning as a generalized persona that shapes the virtual presence of the organization through its corporate website. The research material comprises the corporate websites of several law firms located in the Kemerovo region (Kuzbass). A communicative-pragmatic approach is employed to analyze the discourse, taking into account the pragmatic properties of language units selected according to the specifics of the communicative situation, the participants involved, their social roles, and the electronic medium of information. Language is viewed as a participant in marketing communication and market relations, facilitating the successful delivery of services provided by the organization. It is established that effective marketing communication within the corporate website employs communicative strategies aimed at constructing a positive image of the law firm: strategies for creating an image of a legitimate organization, modeling an authoritative organization, shaping an image of a successful organization, and hyperbolizing the organization’s image. The analysis reveals polycode means of actualizing these strategies, determined by the genre-specific characteristics of the text and the electronic nature of the substrate (the material carrier of the sign).